Transcriptional and Metabolic Profiling of Potato Plants Expressing a Plastid-Targeted Electron Shuttle Reveal Modulation of Genes Associated to Drought Tolerance by Chloroplast Redox Poise - Juan J. Pierella Karlusich (International Journal of Molecular Sciences, 2020)
Water limitation represents the main environmental constraint affecting crop yield worldwide. Photosynthesis is a primary drought target, resulting in over-reduction of the photosynthetic electron transport chain and increased production of reactive oxygen species in plastids. Manipulation of chloroplast electron distribution by introducing alternative electron transport sinks has been shown to increase plant tolerance to multiple environmental challenges including hydric stress, suggesting that a similar strategy could be used to improve drought tolerance in crops. We show herein that the expression of the cyanobacterial electron shuttle flavodoxin in potato chloroplasts protected photosynthetic activities even at a pre-symptomatic stage of drought. Transcriptional and metabolic profiling revealed an attenuated response to the adverse condition in flavodoxin-expressing plants, correlating with their increased stress tolerance. Interestingly, 5–6% of leaf-expressed genes were affected by flavodoxin in the absence of drought, representing pathways modulated by chloroplast redox status during normal growth. About 300 of these genes potentially contribute to stress acclimation as their modulation by flavodoxin proceeds in the same direction as their drought response in wild-type plants. Tuber yield losses under chronic water limitation were mitigated in flavodoxin-expressing plants, indicating that the flavoprotein has the potential to improve major agronomic traits in potato.